Role of Vermicomposting Microorganisms in the Conversion of Biomass Ash to Bio-Based Fertilizers - Turp, Gueldane Asli; Ozdemir, Saim; Yetilmezsoy, Kaan; Oz, Nurtac; Elkamel, Ali (MDPI, 2023)
A high pH, low solubility of bound plant nutrients, and negative impacts on microbial communities are common drawbacks of biomass ash (BA) vermicomposting. In this study, nutrient-rich BA mixed with cow manure was tested at three different application rates to obtain final nitrogen (N), phosphorus (P), and potassium (K) contents of 3.5%, 7.0%, and 10.0% for bio-based fertilizers via vermicomposting. The results showed that all BA blends made with cow manure increased fermentation temperatures and allowed successful worm activity during the subsequent vermicomposting phase. The order of indicator enzyme activities in all vermicomposting samples was urease (220 mu g NH4 g(-1) h(-1)) > beta-glucosidase (95 mu g PNP g(-1) h(-1)) > alkaline phosphatase (91 mu g PNP g(-1) h(-1)) > arylsulfatase (83 mu g PNP g(-1) h(-1)) > acid phosphatase (60 mu g PNP g(-1) h(-1)). As an indicator of nutrient bioavailability, high correlations were observed between enzyme activities and microbial diversity in vermicompost samples. Determination coefficients (R-2) obtained from multiple linear regressions between enzyme activities and bacterial population for T-0, T-1, T-2, and T-3 were determined as 0.90, 0.65, 0.73, and 0.90, respectively. According to a novel metagenome-based approach proposed within the scope of the present study, the stimulatory effects of Flavobacteriales, Burkholderiales, Saccharimonadales, and Pseudomonadales on enzyme activities for the nutrient solubility were found to be significant and positive. The findings of this study demonstrated that worm composting could be a sustainable bio-based technology for the production of slow-release fertilizer from nutrient-rich waste material.
Keywords: biomass ash recycling; vermicomposting; nutrient availability; microbial community; enzyme activity; QUALITY ASSESSMENT; EISENIA-FOETIDA; BIOAVAILABILITY; PHOSPHORUS; STABILITY; BACTERIAL; MATURITY; Science & Technology - Other Topics; Environmental Sciences & Ecology